Indigenous resources contribution and influence of load curve shapes in the optimal growth of Bangladesh electricity sector - Khem Gyanwali; Padam Adhikari; Sonu Khanal; Bikash Adhikari; Debendra Bahadur Raut (Journal of Innovations in Engineering Education, 2023)
The diminishing natural gas resource has turn out to be a severe energy concern for Bangladesh. This study conducts a detailed evaluation of potential pathways for the development of Bangladesh's electricity sector as an emerging economy by developing a capacity expansion model capable of capturing the hourly operational characteristics of diverse power generators and storage technologies, while also identifying the optimal utilization of limited  resources. The simulation results indicate that nuclear energy stands out as the most cost-effective option for achieving sustainable development goals in the absence of substantial opportunities for widespread deployment of renewable energy sources in Bangladesh. However, a significant deployment of solar PV and the incorporation of battery storage could reduce the reliance on nuclear power, contingent on a revision of current land-use policies. The construction of cross-border transmission lines for importing surplus electricity is economically advisable and considering the load curve shape change is found to have significant impact on capacity mix.